Fuzzy Logic supported Consistency Management in DDVEs - Schloss, Hermann; Scholtes, Ingo; Botev, Jean; Esch, Markus; Höhfeld, Alexander; Sturm, Peter (Electronic Communications of the EASST, 2009)
In distributed virtual environments, where avatars permanently change their properties (e.g. their position) or perform modifications on shared objects, inconsistent states may occur due to message latency or concurrent updates. Here, the consistency often falls prey to high interactivity and responsiveness demands. To minimize the presence of inconsistent states or data, the Elastic Consistency model aims at providing an optimal trade-off between consistency and system responsiveness. In this paper we present a Fuzzy Logic driven approach for the computation of this trade-off on the basis of environmental characteristics at the application runtime. Furthermore, we evaluate the impacts of this parameter on consistency and system responsiveness by adjusting the behavior of a classic mutual exclusion algorithm. In this paper we show that an acceptable degree of consistency with respect to required system responsiveness can be efficiently achieved, even when addressing a large number of users.